"Issi my kindt nie" : an ideological study of Matthew 2:16-18. Socio-cultural perspectives of children as sanctioning of violence against them - Muller, Whitney Caroline (Stellenbosch : Stellenbosch University, 2023)
Thesis (MTh)--Stellenbosch University, 2023.